Digital Transformation: A Strategic Imperative for Modern Enterprises - Musahid, Fayza Namira; Fawzi, Fiddini Sharika; Maghfuriyah, Alfi; Hertin, Revita Desi; Wijaya, Hadi; Anjara, Febria; Nugroho, Feri; Listiana, Nora; Istiqomah, Nurul Aslamiah (Indonesian Journal Publisher, 2024)
Digital transformation has become essential for businesses across various sectors, significantly impacting customer relationships, internal processes, and value creation. This paper reviews the critical insights and frameworks related to digital transformation, focusing on strategic alignment, digital maturity, and implementation challenges. It synthesizes findings from recent studies to offer a comprehensive understanding of the process and its implications. Key literature highlights the necessity of a clear, well-defined strategy that integrates digital initiatives with broader business objectives. The study employs a systematic literature review method, collecting data from scientific articles, industry reports, and conference proceedings. It analyzes this data through thematic and comparative approaches to develop a structured roadmap for digital transformation. The findings emphasize the importance of assessing digital maturity, addressing resistance to change, and ensuring interoperability between new and existing systems. Challenges such as organizational resistance and lack of strategic direction are discussed, along with recommendations for a phased implementation approach. Additional insights into the unique challenges faced by SMEs, advocating for tailored digital strategies. The paper concludes that successful digital transformation requires a holistic approach that encompasses strategy, technology, and organizational culture. Future research should focus on providing detailed guidelines for SMEs and exploring the long-term effects of digital transformation on organizational culture and employee engagement.